Construction innovation diffusion in the Russian Federation: Barriers, drivers and coping strategies. Issue 3 (13th July 2015) - Suprun, Emiliya V.; Stewart, Rodney A.
Abstract : Purpose: – The aim of this study is to explore the current situation in the Russian construction industry and the obstacles, drivers and strategies that affect innovation implementation most significantly. The Russian construction industry is highly conservative and is often criticised for its lack of innovation. Construction firms invest relatively little in innovation adoption, development of new ideas and formal research and development. Design/methodology/approach: – This study utilised an extensive literature review followed by a questionnaire survey incorporating some post hoc interviews with 52 experts from the Russian architecture, engineering and construction industry to identify the most significant drivers, enablers, barriers and strategies related to innovation diffusion in construction. Findings: – Findings indicated that economic and financial difficulties, as well as inappropriate legislation, are the most significant barriers to innovation. Financial incentives, legislative improvements and the promotion of alternative construction procurement methods were viewed as the most critical strategies to improve the current lacklustre rate of innovation diffusion. Originality/value: – While there is anecdotal evidence that the Russian construction industry is lagging in terms of technological advancement, its closed nature means that there is still little reported evidence on what are the main barriers to innovation diffusion in this country. Hence, there is a lack of focus on innovation diffusion rates in different construction sectors, such as building and civil infrastructure and limited consideration on how effectively the research and development sector contributes to innovation.